2018
DOI: 10.1155/2018/6306542
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium as a Potential Target for Treatment of Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) was previously ascribed to weaken defective medial arterial/adventitial layers, for example, smooth muscle/fibroblast cells. Therefore, besides surgical repair, medications targeting the medial layer to strengthen the aortic wall are the most feasible treatment strategy for AAA. However, so far, it is unclear whether such drugs have any beneficial effect on AAA prognosis, rate of aneurysm growth, rupture, or survival. Notably, clinical studies have shown that AAA is highly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 105 publications
(115 reference statements)
0
49
0
Order By: Relevance
“…Previous ex vivo studies demonstrated more marked vascular permeability in patients with AAAs and found an association with a higher rupture risk 4,5 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous ex vivo studies demonstrated more marked vascular permeability in patients with AAAs and found an association with a higher rupture risk 4,5 .…”
Section: Discussionmentioning
confidence: 95%
“…In particular, aneurysms have been described as a weakening of the aortic wall due to SMC-specific defects, resulting in the dissection of the vessel ( Takeda et al, 2018 ). Only recently have a few studies started considering the endothelium as a potential therapeutic target in aortic pathologies ( van de Pol et al, 2017 ; Sun et al, 2018 ). The close proximity of ECs with SMCs makes their cross-talk essential for aortic development and homeostasis ( Lilly, 2014 ; Stratman et al, 2017 ; Segers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, aneurysms have been described as a weakening of the aortic wall due to SMC-specific defects, resulting in the dissection of the vessel (Takeda et al, 2018). Only recently have a few studies started considering the endothelium as a potential therapeutic target in OFT and aortic pathologies (van de Pol et al, 2017; Sun et al, 2018). The close proximity of ECs with SMCs makes their cross-talk essential for aortic development and homeostasis (Lilly, 2014; Stratman et al, 2017; Segers et al, 2018).…”
Section: Introductionmentioning
confidence: 99%